Annuloplasty band implantation in adults with partial atrioventricular septal defect: a propensity-matched study. (24th October 2017) - Zhou, Tianyu; Li, Jun; Lai, Hao; Zhu, Kai; Sun, Yongxin; Wang, Yongshi; Ding, Wenjun; Hong, Tao; Wang, Chunsheng
Abstract: OBJECTIVES: The incidence of recurrent left atrioventricular valve (LAVV) regurgitation is generally high after repair of partial atrioventricular septal defect (AVSD). This study aimed to evaluate the effect of implanting an additional annuloplasty band into the LAVV during partial AVSD repair and to assess the late outcomes of recurrent LAVV regurgitation. METHODS: This study enrolled 133 patients who underwent repair of partial AVSD at our institution from January 2005 to December 2015. All patients underwent repair of the ostium primum atrial septal defect and closure of the LAVV cleft; 37 patients underwent additional annuloplasty band implantation. To minimize differences in preoperative data, propensity score matching was used to identify 33 well-matched patient pairs. RESULTS: Cardiopulmonary bypass time and aorta cross-clamp time were significantly longer in the band implantation group ( P < 0.05). The 2 groups had similar durations of intensive care and hospital stay ( P > 0.05). There was 1 in-hospital death in the band implantation group. During follow-up, conduction block occurred in 6 patients in each group. After follow-up of more than 10 years, freedom from late recurrent LAVV regurgitation was 91% in the band implantation group and 57% in the isolated cleft closure group ( P < 0.05). In patients with preoperative severe regurgitation and moderate/mild regurgitation, the rates of freedom from recurrent LAVV regurgitation were 85% and 37%, respectively ( P < 0.05). CONCLUSIONS: In patients with moderate/severe LAVV regurgitation or severe annular dilation, additional band implantation significantly reduces the incidence of recurrent regurgitation and improves long-term outcomes.